A case report of schizophrenia with an atypical presentation of body dysmorphic disorder (Bangladesh Journal of Psychiatry, 2020)
Although body dysmorphic disorder is a psychiatric disorder. Sometimes, it can be a variant of a variety of psychiatric syndromes like schizophrenia, mood disorders, OCD etc. Here is an atypical case report of a 28 years old male patient who presented with body dysmorphic disorder later on diagnosed as having schizophrenia. The difficult part in this diagnosis is to make the difference between the psychotic and the non-psychotic form of the disorder. Finally, its successful treatment with antipsychotic drugs, thus contributing to what has been documented on the subject.Bang J Psychiatry 2018;32(2): 40-43